2011
DOI: 10.1111/j.1600-0870.2010.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Air ForceWeather Agency’s mesoscale ensemble: scientific description and performance results

Abstract: A B S T R A C TThis work evaluates several techniques to account for mesoscale initial-condition (IC) and model uncertainty in a short-range ensemble prediction system based on the Weather Research and Forecast (WRF) model. A scientific description and verification of several candidate methods for implementation in the U.S. Air Force Weather Agency mesoscale ensemble is presented. Model perturbation methods tested include multiple parametrization suites, landsurface property perturbations, perturbations to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 36 publications
5
81
0
Order By: Relevance
“…This is because they indicate the contribution of each individual model in the mixture for the representation of the real system output. Posterior estimates for the weight functions t k p¨qu can be computed asˆ 15) along with the associated standard errors according to the Markov chain CLT [40]. Moreover, the weight functions allow the determination of a reasonable input space partition tX k u K k"1 where each sub-region X k " tx P X | k pxq " maxp 1 pxq, ..., K pxqqu includes the input values that model S pkq is more preferable to be used than the rest.…”
Section: Inference Calibration and Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because they indicate the contribution of each individual model in the mixture for the representation of the real system output. Posterior estimates for the weight functions t k p¨qu can be computed asˆ 15) along with the associated standard errors according to the Markov chain CLT [40]. Moreover, the weight functions allow the determination of a reasonable input space partition tX k u K k"1 where each sub-region X k " tx P X | k pxq " maxp 1 pxq, ..., K pxqqu includes the input values that model S pkq is more preferable to be used than the rest.…”
Section: Inference Calibration and Predictionmentioning
confidence: 99%
“…Moreover, higher grid spacing does not necessarily lead to more accurate simulations because WRF is sensitive to other physical parametrizations which is uncertain how they are affected by the grid spacing. Combination of physics variability is expected to result better predictions in climate models [15]; hence interest lies in combining suitably these computer models in order to integrate the associated physics and fidelity variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of accounting for model errors is to introduce stochastic perturbations in some aspects of the parameterization schemes adopted by the ensemble members (multi-physics ensembles [239] offer another approach to the problem).…”
Section: Stochastic Boundary-layer Parameterizationmentioning
confidence: 99%
“…Even if the calibration produces realistic regional means, important spatial variability may not be reproduced if observed spatial patterns from high-resolution measurements are not utilized in the global tuning. Hacker et al (2011) evaluated the impacts of initial condition and model parameterization uncertainties on a WRF-based ensemble prediction system and found that different combinations of parameterization schemes associated with perturbed parameters could generate the most skillful ensemble prediction.…”
mentioning
confidence: 99%